2021
DOI: 10.1109/access.2021.3096287
|View full text |Cite
|
Sign up to set email alerts
|

Partial Discharge Pattern Recognition of Transformers Based on the Gray-Level Co-Occurrence Matrix of Optimal Parameters

Abstract: The partial discharge (PD) is the most common fault of transformers, which is the main factor affecting the stable operation of transformers. Therefore, the PD should be monitored and identified timely to improve the reliability of the transformers. In this paper, a transformer PD pattern recognition algorithm based on the gray-level co-occurrence matrix of optimal parameters and support vector machine (GLCMOP-SVM) is proposed. Firstly, the GLCM of optimal parameters (GLCMOP) is proposed to be determined by ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Let (W , b en ) and (W T , b de ) be the parameters of encoder and decoder, respectively, then the code vector H in latent space can be calculated by f (X), and the output X of AE is obtained by g(H). The goal of AE is to minimize the difference between X and X, thus the objective function can be written as: Cross−entropy loss function (19) By stacking multiple AE models sequentially, the stacked AEs network can be obtained, which is a typical DAN model. Besides, there are many other improved versions of DAN models [182], such as the SAE, DAE, CAE, VAE, etc.…”
Section: B Dan-based Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Let (W , b en ) and (W T , b de ) be the parameters of encoder and decoder, respectively, then the code vector H in latent space can be calculated by f (X), and the output X of AE is obtained by g(H). The goal of AE is to minimize the difference between X and X, thus the objective function can be written as: Cross−entropy loss function (19) By stacking multiple AE models sequentially, the stacked AEs network can be obtained, which is a typical DAN model. Besides, there are many other improved versions of DAN models [182], such as the SAE, DAE, CAE, VAE, etc.…”
Section: B Dan-based Methodsmentioning
confidence: 99%
“…The results showed that compared with existing methods using statistical features, the LBP or HOG features extracted in that paper can increase the average accuracy rate by more than 10%. In [19], Sun et al proposed an improved texture feature extraction method namely GLCMOP and applied it to the 2-D PRPD grayscale images. To reduce the influence of noise on the PRPS graphs, Li et al introduced the SURF algorithm to extract the feature points and feature descriptors of the PRPS grayscale images [20].…”
Section: ) Phase-based Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The above matrix specifies the spatial relationship between the intensity of the image pixels. x(n) is the gray level co-occurrence matrix component in the image 23 fw(x)=n=|x(n)|2.…”
Section: L2s Segmentation Algorithm Based On Image Local Energymentioning
confidence: 99%
“…The above matrix specifies the spatial relationship between the intensity of the image pixels. xðnÞ is the gray level co-occurrence matrix component in the image 23 E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 0 6 ; 1 1 7 ; 5 3 2…”
Section: L2s Segmentation Algorithm Based On Image Local Energymentioning
confidence: 99%